2009
DOI: 10.1088/0957-4484/20/32/325706
|View full text |Cite
|
Sign up to set email alerts
|

The experimental investigation of thermal conductivity and the Wiedemann–Franz law for single metallic nanowires

Abstract: A new method for the measurement of thermal conductivity of electrically conducting single nanowires is presented. First experimental investigations are focused on the thermal conductivity of metallic Pt nanowires with a diameter of (typically) 100 nm and a length of 10 microm. Thermal conductivity data are compared with measurements of electrical conductivity in order to test the Wiedemann-Franz law for metallic nanowires. Compared to the bulk values at room temperature, electrical and thermal conductivities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
98
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(109 citation statements)
references
References 18 publications
11
98
0
Order By: Relevance
“…The W4f core-level binding energy displays a rather strong dependency on the oxidation state of the W atom. Bonding to oxygen atoms shifts these two peaks to higher binding energies from the usual position of metallic tungsten (31.4 and 33.6 eV) to 36 eV [29,30]. It should be noted that given the rather high energies of the available X-ray excitation (1253.6 eV), the surface sensitivity for W4f photoelectrons is not very high [30].…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 92%
See 1 more Smart Citation
“…The W4f core-level binding energy displays a rather strong dependency on the oxidation state of the W atom. Bonding to oxygen atoms shifts these two peaks to higher binding energies from the usual position of metallic tungsten (31.4 and 33.6 eV) to 36 eV [29,30]. It should be noted that given the rather high energies of the available X-ray excitation (1253.6 eV), the surface sensitivity for W4f photoelectrons is not very high [30].…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 92%
“…By increasing the growth time, the conductivity of the sample increases, this may be due to an increase in the number of nanowires on the sample surface which increases the available free charge carriers. On the other hand, based on experimental results [30][31][32]35], it was found that the number and size of nanowires have apparent influence on the electrical properties, which is in good agreement with the theoretical models [33,34]. For studying the electrical conductivity in nanostructures, based on the Matthiessen's and Bloch-Grü-neisen theory [34], the electrical resistivity depends on two factors: (1) the residual resistivity (due to structural scatterings caused by grain boundary, impurity and surface).…”
Section: Sem Analysismentioning
confidence: 99%
“…All measurements were performed in high vacuum, so that thermal convection cannot influence the results. Thermal radiation plays a minor role in the used temperature range [12]. In order to perform this measurement, a well defined heater line is required.…”
Section: Thermal Conductivity Measurementmentioning
confidence: 99%
“…It has been applied to the study and development of nanostructured materials, such as superlattices [4] [5], and micro/nano electronic devices, for example, nanowires [6] [7].…”
Section: Introductionmentioning
confidence: 99%